Molecular Detection of Carbapenem Resistance in Multi-Drug Resistant Pseudomonas aeruginosa from Patients and Fomites in Federal Medical Centre Keffi, Nigeria - I., Abdulmumin R.; B., Ngwai Y.; H., Nkene I. (African Journal of Clinical Medicine and Pharmacy Research, 2025)
This study is the aimed at the molecular detection of carbapenem resistance in multidrug resistant Pseudomonas aeruginosa from patients and fomites in Federal Medical Centre, Keffi, Nigeria. The study was carried out in Federal Medical Centre, Keffi (FMCK), Nigeria, between the period of February- August, 2020. Material and Methods: A total of 365 samples comprising 265 clinical (urine, wound swab, eye swab, ear swab, high vigal swab (HVS) and endocervical swab (ECS)) and 100 fomites samples were collected from Federal Medical Centre, Keffi, Nigeria. Results: Out of 365 clinical and formitesscreened, FMCK had overall occurrence 42 (11.5%) both in clinical andfomite samples examined. The isolates from both formites and clinical samples were more resistant to nalidixic acid (85.7%) and ampicilin (71.4%) but less resistant to imipenem (33.3%), ofloxacin (42.8%) and streptomycin (45.2%).The occurrence of carbapenemase producing imipenem resistant isolates was 28.5%.The occurrence of blaKPC was 100%.The occurrences of blaVIM and blaOXA genes were 75% each. The occurrence of isolates with co-carriage of blaVIM/KPC/OXA (75%) was higher than blaVIM/KPC, blaKPC/OXAand blaVIM/OXA (50%). Conclusions: The occurrence of the isolates from fomites and clinical samples was high and most antibiotics tested were not effective against the P. aeruginosa isolates.